Governance of the flood disaster framework in Malaysia: a way forward in enabling information technology knowledge sharing - Maidin, Siti Sarah; Othman, Marini; Ahmad, Mohammad Nazir; Yahya, Norzariyah (Institute of Advanced Scientific Research, Inc., 2019)
Particularly in the field of Flood Management, poor governance results in weakness when tracking and monitoring flooding activities and systems, the poor mitigation of flood risks, and the inefficient use of both given and invested resources. This study proposes a framework for governing flood disaster management within Malaysia. The Control Objective for Information and Related Technologies (COBIT), the Hyogo Framework for Action, and the Sendai Framework for Disaster Risk Reduction, have all been used as guiding principles for the proposed framework’s development. A qualitative field study was deployed for identifying baseline practices in governing flood response in Malaysia. As a result, Governance for Flood Disaster framework, consisting ten building block components, was constructed. The framework capitalized on the strength of elements found from the existing practices documented by the National Security Council’s Directive and the Kemaman Standard Operating Procedure, while filling up identified gaps by applying the principles and spirit of COBIT, and the Hyogo and Sendai frameworks. The framework was assessed in regards to its conformance, completeness and acceptance, and was further validated using the techniques of expert opinions. From the validation result, it can be noted that the framework has been accepted without any changes or amendments. It is hoped that further studies can be undertaken to develop and establish each of the components within the framework, and that the framework itself can be further tested and improved on over time. © 2019, Institute of Advanced Scientific Research, Inc. All rights reserved.